Intrahousehold Resource Allocation in Côte D'ivoire: Social Norms, Separate Accounts and Consumption Choices - Esther Duflo; Christopher Udry (Yale University, Economic Growth Center, 2003)
In Côte d'Ivoire, as in much of Africa, husbands and wives farm different crops on separate plots. These different crops are differentially sensitive to particular kinds of rainfall shocks. We find that conditional on overall household expenditure, the composition of expenditure is sensitive to the gender of the recipient of a rainfall shock. For example, rainfall shocks associated with high women's income shift expenditure towards food. Social norms constrain the use of profits from yam cultivation, which is carried out by men. Correspondingly, we find that rainfall-induced fluctuations in income from yams are transmitted to expenditures on education and food, not to expenditures on private goods. We reject the hypothesis of complete insurance within households, even with respect to publicly observable weather shocks. Different sources of income are allocated to different uses depending upon both the identity of the income earner and upon the origin of the income.
Keywords: O12; D13; 330; Intra-household Allocation; Insurance; Social Norms; Mental Accounts; Haushaltsökonomik; Ackerbau; Agrareinkommen; Verbraucherausgaben; Geschlecht; Schätzung; Elfenbeinküste; Soziale Norm